EDUCATIONAL OBJECTIVES IN INTELLIGENT TUTORS FOR COMMUNICATION SKILLS - CIPRIAN CUCU (Annals of the University of Petrosani: Economics, 2015)
Intelligent Tutoring Systems have been successfully used to simulate human tutoring in various fields such as mathematics, physics or computer programming. The current paper discusses some of the particularities of designing such systems for the education of communication skills, specifically in a business setting (customer relations, employee communications etc). Since communication is an ill-defined domain (i.e. does not provide a systematic method to obtain a solution), various challenges arise. One of these challenges is the design of educational objectives – the module built on top of the system that would check the users' actions against predefined patterns and would provide the users with feed-back accordingly.